Release of fragrances from cotton functionalized with carbohydrate-binding module proteins - Gonçalves, Filipa Daniela Gomes (2019)
Perspiration as a response to daily activity and physical exercise results in unpleasant odors that cause social unrest and embarrassment. To tackle it, functional textiles incorporating fragrances could be an effective clothing deodorizing product. This work presents two strategies for the release of -citronellol from functionalized cotton with carbohydrate-binding module (CBM)-based complexes (OBP::GQ20::CBM/-citronellolapproach 1 and CBM::GQ20::SP-DS3-liposome/-citronellolapproach 2). CBM from Cellulomonas fimi was fused with the odorant-binding protein (OBP::GQ20::CBM) and with an anchor peptide with affinity to the liposome membrane (CBM::GQ20::SP-DS3). In approach 1, OBP fusion protein served as a fragrance container, whereas in approach 2, the fragrance was loaded into liposomes with a higher cargo capacity. The two strategies showed a differentiated -citronellol release profile triggered by an acidic sweat solution. OBP::GQ20::CBM complex revealed a fast release (31.9% and 25.8% of the initial amount, after 1.5 and 24 h of exposure with acidic sweat solution, respectively), while the CBM::GQ20::SP-DS3-liposome complex demonstrated a slower and controlled release (5.9% and 10.5% of the initial amount, after 1.5 and 24 h of exposure with acidic sweat solution, respectively). Both strategies revealed high potential for textile functionalization aimed at controlled release of fragrances. The OBP::GQ20::CBM/-citronellol complex is ideal for applications requiring fast release of a high amount of fragrance, whereas the CBM::GQ20::SP-DS3-liposome/-citronellol complex is more suitable for prolonged and controlled release of a lower amount of -citronellol.